Synthesis and tribological behaviour of oleic acid‐capped lanthanum borate/graphene oxide nanocomposites. (1st August 2016) - Li, Wei; Cheng, Zhi‐Lin; Liu, Zan
Abstract: The lanthanum borate/graphene oxide (LB/GO) nanocomposites were obtained by GO decorated by LB using an eco‐friendly hydrothermal method. For improving the oil solubility of the LB/GO nanocomposites, the oleic acid (OA)‐capped LB/GO (OA–LB/GO) nanocomposites were achieved. The as‐prepared nanocomposites were determined by a series of characterisations such as Fourier transform‐infrared spectroscopy (FT‐IR), X‐ray powder diffraction (XRD), Raman, UV‐vis, transmission electron microscopy (TEM) and SEM. The results indicated that most of LB nanoparticles with the size of 50–100 nm were well loaded on the surface of GO nanosheets. In addition, the tribological properties of the as‐prepared nanocomposites were tested by a four‐ball friction machine. The results demonstrated that the OA–LB/GO nanocomposites were of good anti‐wear ability and excellent load‐carrying capacity. Copyright © 2016 John Wiley & Sons, Ltd.